Síntese de 4-(fur-2-il)- e 4-(tien-2-il)-pirimidinas a partir de β-Alcoxivinil trifluormetil cetonas - Pizzuti, Lucas (2005)
The cyclocondensation of the 1,1,1-trifluoro-4-methoxy-4-(2-heteroaryl)-3-buten-2-ones (heteroaryl = furyl and thienyl) with urea and amidines (acetamidine, benzamidine, guanidine, 1H-pyrazole-1-carboxamidine and 2-methyl-2-thiopseudourea) for synthesis of two 4-(2-heteroaryl)-6-trifluoromethylpyrimidinones and a series of ten 4-(2-heteroaryl)-6-trifluoromethylpyrimidines is reported. The reaction of the 1,1,1-trifluoro-4-methoxy-4-(2-heteroaryl)-3-buten-2-ones with urea was carried out in the presence of boron trifluoride etherate as a catalyst, at 50°C for 20 hours. The reactions of the same substracts with amidines were carried out in the presence of a 1 M solution of sodium hydroxide at r.t.-50°C for 1 hour. Under this conditions, only aromatic pyrimidines were obtained in 48-67%.